Natural ventilation and indoor air quality in educational buildings: experimental assessment and improvement strategies - Almeida, Ricardo (2016)
Indoor environmental conditions in classrooms, in particular temperature and indoor air quality, influence students’ health, attitude and performance. In recent years, several studies regarding indoor environmental quality of classrooms were published and natural ventilation proved to have great potential, particularly in southern European climate. This research aimed to evaluate indoor environmental conditions in eight schools and to assess their improvement potential by simple natural ventilation strategies. Temperature, relative humidity and carbon dioxide concentration were measured in 32 classrooms. Ventilation performance of the classrooms was characterized using two techniques, first by fan pressurization measurements of the envelope airtightness and later by tracer gas measurements of the air change rate assuming different envelope conditions. A total of 110 tracer gas measurements were made and the results validated ventilation protocols that were tested afterward. The results of the ventilation protocol implementation were encouraging and, overall, a decrease on the CO2 concentration was observed without modifying the comfort conditions. Nevertheless, additional measurements must be performed for winter conditions.